If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xsquare + 6x = 6 Solving 3aeqrsux + 6x = 6 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6x' to each side of the equation. 3aeqrsux + 6x + -6x = 6 + -6x Combine like terms: 6x + -6x = 0 3aeqrsux + 0 = 6 + -6x 3aeqrsux = 6 + -6x Divide each side by '3eqrsux'. a = 2e-1q-1r-1s-1u-1x-1 + -2e-1q-1r-1s-1u-1 Simplifying a = 2e-1q-1r-1s-1u-1x-1 + -2e-1q-1r-1s-1u-1 Reorder the terms: a = -2e-1q-1r-1s-1u-1 + 2e-1q-1r-1s-1u-1x-1
| 2(4x+7)-8(3x-4)=6(2x+3)-7(2x-3) | | 10x+72=450 | | 2(4x+7)-8(3x-4)=6(2x+3)-7(2x-3) | | X+30+31=90 | | g^2=35 | | 6x+2y+4=4 | | X-20=5(7+4) | | 2/5x-3=-15 | | 99+0.45x=2.19x | | -5.5x+0.56=-1.6 | | f(x)=x^2-1.25x+0.390625 | | 388=2(3x-8)+2(5x+9) | | 7m-(m+80)= | | 189=9(a+6) | | 2(3x-5)+9x=48-4(x+2)+16 | | g^2=31 | | 12+2.15x=2.45x | | 2(3x-2)=-16 | | 5z=2(2z+3) | | -180=10(-4+n) | | 12+2.15=2.45 | | f(x)=20-4x | | 19+0.10d=21+0.05d | | x^4-47x^2-98=0 | | r+11+8r=29+3r | | 8r^3=200r | | 15(7.35-0.58(-1.25+-2)-0.061)+0.4(-1.25+-2)+2-19.1+3(7.35-0.58(-1.25+-2)-0.06)+10(-1.25+-2)-1-23.25=90 | | -2(-8-2n)+2n=-4-2(1-2n) | | 40x-32x=0 | | 3(k-1)-3(2k+2)=2 | | x^4=47x^2-98 | | 34.932=4.92 |